PENERAPAN METODE DEMONTRASI BERBANTUAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN PERHATIAN DAN PRESTASI BELAJAR - Mashannudin Mashannudin (DIADIK, 2020)
This study aims to describe the application of demonstration methods assisted by Audio Visual media to increase student attention and learning achievement. The research conducted was Classroom Action Research which was carried out in three cycles, each cycle through the stages of planning, implementation, observation and reflection. The subjects of the study were grade VI students of SD Negeri 36 Lahat. The instruments used were observation sheets and test sheets. Data collection techniques by observation and test, while the experimental class only tested the demonstration method. Data analysis was performed using a t test and a classical average value. Based on the analysis of the data of this study it was concluded that (1) The application of an audio visual assisted demonstration method can increase student attention; (2) The application of an audio visual assisted demonstration method can improve student learning achievement; (3) There is an effective use of audio visual assisted demonstration methods to improve student achievement in natural science subjects grade VI at 36 Public Schools in Lahat